Pengaruh Tax Morale Terhadap Niat Untuk Patuh Calon Wajib Pajak Dengan Kesadaran Pajak Sebagai Variabel Moderasi: (Studi Kasus Pada Mahasiswa UST Sebagai Calon Wajib Pajak) - Dewi Kusuma Wardani; Yuli Prihatni; Ayu Wulandari (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
This study aims to examine whether tax morale affects the obedient intentions of prospective taxpayers with tax awareness as a moderating variable. This study uses descriptive quantitative methods and primary data using a questionnaire. The number of samples in this study were 100 respondents from the undergraduate program at Tamansiswa University, Yogyakarta. Sampling in this study using convenience sampling technique. This study provides results that tax morale has no effect on tax compliance intentions, tax awareness cannot strengthen the positive effect of tax morale on tax compliance intentions.